1989
DOI: 10.1016/0378-1097(89)90364-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall constituents of Microcystis sp. PCC 7806

Abstract: Cell walls of Microcystis sp. PCC 7806 were purified from cell homogenates by sucrose density centrifugation and Triton X-100 extraction. The outer membrane contained carotenoids, two major peptidoglycan-associated proteins (Mr 49,000 and 52,000), and lipopolysaccharide (LPS) as indicated by the presence of 3-hydroxy fatty acids (3-OH-14:0, 3-OH-16:0, 3-OH-18:0), 4-oxo-18:0 fatty acid, and GlcN as lipid A components in addition to rare O-methyl sugars (2-O-methyl-6-deoxyhexoses I and II). The peptidoglycan (A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In cyanobacteria carotenoids such as zeaxanthin, echinenone and carotenoid glycosides such as myxoxanthophyll are found in the outer membrane [36][37][38] and the cell wall [39][40][41][42][43][44]. High light or other environmental stresses results in an increase in the types and quantities of cyanobacterial carotenoids in these locations.…”
Section: Carotenoid Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…In cyanobacteria carotenoids such as zeaxanthin, echinenone and carotenoid glycosides such as myxoxanthophyll are found in the outer membrane [36][37][38] and the cell wall [39][40][41][42][43][44]. High light or other environmental stresses results in an increase in the types and quantities of cyanobacterial carotenoids in these locations.…”
Section: Carotenoid Transportmentioning
confidence: 99%
“…The cell wall and the outer membrane of cyanobacteria are rich in protein as well as carotenoids [36][37][38][39][40][41][42][43][44]. Some of these proteins may be the OCP or its paralogs.…”
Section: Component Of Photoprotective Structuresmentioning
confidence: 99%
“…(Schmidt et al 1980a, Schrader et al 1981, Woitzik et al 1988, Synechocystis sp. (Schmidt et al 1980b, Jurgens & Weckesser 1985b, Microcystis aeruginosa (Raziuddin et al 1983, Martin et al 1989, Microcystis sp. , Agmenellum quadruplicatum (Buttke & Ingram 1975) and Gloeobacter violaceus (Schneider & Jurgens 1991), and also filamentous forms, e.g.…”
Section: Cell Envelopementioning
confidence: 99%
“…Those studies showed similarities between LPS from cyanobacteria and Gram-negative bacteria, but considerable diversity in their chemical composition and biological characteristics, even between strains, has been reported. For example, 2-keto-3-deoxyoctonate, although considered a specific marker for LPS, was absent in Anabaena variabilis, Anabaena flos-aquae, Synechocvstis sp., Schizothrix calciola, Microcystis aeruginosa and Synechococcus strains (Weckesser et al 1974, Wang & Hill 1977, Keleti et al 1979, Schmidt et al 1980a, b, Schrader et al 1981, Martin et al 1989, and was found in small or negligible quantities in Agmenellurn quadruplicaturn, Anacystis nidulans, Phormidium up. and Synechococcus strains (Weise et al 1970, Buttke & Ingram 1975, Katz et al 1977, Mikheyskaya et al 1977, Schmidt et al 1980a, Resch & Gibson 1983.…”
Section: Cell Envelopementioning
confidence: 99%
See 1 more Smart Citation